Empreendedorismo social e vazios institucionais: mecanismos de desenvolvimento e criação de valor - Silva, Laíse do Nascimento (2024)
Social enterprises are based on a phenomenon that has received academic attention since they start from the construction of business models aimed at the needs of society based on solutions based on social problems or even the discovery of new business ideas, bringing the generation of social value. To integrate discussions about this growing phenomenon, there is the theory of institutional voids Voids as an advance in literature in the organizational context and which can be adapted to understand social changes amid institutional weaknesses that affect society, causing inequalities and reflecting on people's conditions. Thus, the present study analyzed how social enterprises create social value in environments with Institutional Empties. To this end, it adopted an exploratory and descriptive qualitative methodology through the multiple case studies proposed by Eisenhardt (1989). The study was conducted in 05 social enterprises, with an interview guide applied to entrepreneurs, managers, and employees, in addition to some observation visits. In total, 05 interviews were obtained with those responsible for the organization and 07 employees from all participating enterprises. The results revealed that the enterprises operate in different areas: Education, environment, health, and agriculture. Institutional voids were noticed as there was no government support, introducing difficulties, mainly regarding resources and structure. Furthermore, institutions have defined projects and objectives that emerge from social value generation, seeking to contribute to improving the needy community. The analysis of social enterprises operating in Piauí amid environments of Institutional Voids significantly highlights the capacity of Social Entrepreneurship to fill gaps left by formal institutions and, consequently, generate significant social value. In short, each enterprise studied reveals the vitality and relevance of this phenomenon, not only as an adaptive response to institutional deficiencies but also as a catalytic force to promote substantial social transformations. Creating social value is not just a side effect but a central objective that drives these enterprises to work tirelessly to improve the quality of life in their communities.